2004
DOI: 10.1007/s00253-004-1630-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization in Pseudomonas putida Cg1 of nahR and its role in bacterial survival in soil

Abstract: Sequencing, RFLP analyses and experiments utilizing a lacZ transcriptional reporter fused to the promoter regions of nahR and nahG in Pseudomonas putida Cg1 confirmed that regulation of naphthalene degradation in both P. putida Cg1 and the type strain, P. putida NCIB 9816-4, is consistent with that of NAH7 from P. putida G7. Two nahR knockout strains (RK1 and Cg1-NAHR from P. putida NCIB 9816-4 and Cg1, respectively) showed a growth defect in the presence of naphthalene as sole carbon and energy source. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…4); (iii) the phenotype of a nagR mutant (strain CJN110; Fig. 5) matches that of other naphthalene degraders with mutations in LysRtype regulatory genes (33,38); and (iv) the expression pattern of a portion of the genes in strain CJ2 resembles that of other naphthalene degraders (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
“…4); (iii) the phenotype of a nagR mutant (strain CJN110; Fig. 5) matches that of other naphthalene degraders with mutations in LysRtype regulatory genes (33,38); and (iv) the expression pattern of a portion of the genes in strain CJ2 resembles that of other naphthalene degraders (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
“…5 ). Several naphthalene carbolic proteins have been identified in Pseudomonas sp., including NahR, NahG, NahU, and NahW 15 , 38 40 , and these proteins imparted resistance to the toxic effects of naphthalene, hence these bacterial cells can persistent in soils where naphthalene occurs at high concentrations 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both the nah and bph operons for naphthalene and biphenyl degradation, respectively, contain multiple LysR-type regulator binding sites which allow for independent transcription of upper and lower pathway genes (Huang & Schell, 1991;Watanabe et al, 2003Watanabe et al, , 2000. The importance of regulating relative levels of catechol degradation activity was hinted at by Park & Madsen (2004) who have shown that regulation by NahR, which preferentially upregulates the lower pathway genes encoding degradation of catechol, was critical for the survival of naphthalene degraders in naphthalene-contaminated soil. This contrasts with the monocistronic nature of the tod operon and the absence of a supplementary promoter directly upstream of todE.…”
Section: Discussionmentioning
confidence: 99%